Individual monitoring of aerobic and anaerobic performance of hockey players during the annual training cycle - Bolotin, A. E.; Poniasov, O. E.; Zyukin, A. V.; Nguyen, K. Z. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to increase functional readiness based on individual assessment of aerobic and anaerobic performance of hockey players throughout the annual training cycle.